The Martyr Motif in the Gospel According to Mark - Riddle, Donald W. (The journal of religion, 1924)
Historical method in the study of early Christianity finds in the observation of purpose a key to the understanding of the documentary sources. Applying this criterion to the Gospel according to Mark, the distribution of materials and the emphasis upon the passion story suggest that a major purpose of the work was the presentation of Jesus as martyr. In other Christian writings, the purpose of control in situations similar to that in which Mark appeared developed the martyrology as a literary type. The interest in Jesus as martyr, so readily observable in Mark, gives to it the character of a primitive martyrology. In this capacity it appears to have successfully met the situation for which it was intended.